2020
DOI: 10.1021/acsomega.0c02443
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of Lignin Particles and Their Ultraviolet Protection Ability in PVA Composite Film

Abstract: Recently, lignin utilization in advanced applications has gained much interest. Due to the limitation of the current use of standard lignin, lignin particles have recently gained attention in overcoming the challenge. In this work, the spherical lignin particles obtained from organosolv lignin (OL) were prepared using the dialysis method with tetrahydrofuran (THF) or ethanol as the solvent. From the result, it was found that the types of lignin and solvent, initial lignin concentration, and stirring rate stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 45 publications
3
25
0
Order By: Relevance
“…To the best of the author’s knowledge, this is the smallest particle size of wood-derived LN and is >3 times smaller than the particle size of LN (1000 nm at 0.01 g·mL –1 ) obtained from sugarcane. 18 22 In the case of K-LN, the particle size could not be measured using DLS because it is water insoluble.…”
Section: Resultsmentioning
confidence: 99%
“…To the best of the author’s knowledge, this is the smallest particle size of wood-derived LN and is >3 times smaller than the particle size of LN (1000 nm at 0.01 g·mL –1 ) obtained from sugarcane. 18 22 In the case of K-LN, the particle size could not be measured using DLS because it is water insoluble.…”
Section: Resultsmentioning
confidence: 99%
“… 70 Similarly, effective UV-B blocking was found when lignin was added at a higher concentration (3 wt %) into the PVA film, whereas UV-A transmittance was still not totally barred. 71 Furthermore, Parit et al reported that complete UV-A and UV-B blocking was obtained in the cellulose nanocrystal (CNC)/lignin film at a 10 wt % softwood kraft lignin loading. 72 A lower lignin addition to bar all UV transmittance was reported by Zhang et al when applying 5 wt %, equal to 0.25% (w/v), lignin nanomicelle (LNM) incorporation into a PVA/LNM composite film.…”
Section: Resultsmentioning
confidence: 99%
“…Nano-and microscale lignin particles have gained a great deal of interest in the preparation of lignin-based polymeric materials, due to their spherical shape and colloidal stability in comparison to raw lignins. 35,36,37,38 For instance, colloidal lignin nanoparticles (LNPs) can remain flowable at high concentrations (50 wt % or more) and act as reinforcing agents to improve the UV shielding and antioxidant properties in hydrophilic polymeric matrices such as CNF, 39,40 poly(vinyl alcohol) (PVA), 41,41,43 chitosan 44 or polylactic acid (PLA). 45 Besides the possibility to be used as reinforcing agent, LNPs are also finding new applications as carriers for biologically active substances such as drugs, pesticides or enzymes.…”
Section: Introductionmentioning
confidence: 99%